The Role of Religious Brand Community Support in Enhancing Value Co-Creation in Religio-Centric Markets: Case Study in Religious Tourism Destinations - Anita Kristina; Mohammad Sofyan Yasin (Journal of Sharia Economics, Banking and Accounting, 2026)
The urgency of this research stems from the phenomenon of religiously-based Packaged Drinking Water in tourism destinations, presenting a unique value co-creation model within Islamic economics. This study aims to analyze the role of religious brand community support in enhancing value co-creation for "Martajasah" Packaged Drinking Water in the Syaikhona Kholil Bangkalan Religious Tourism Area. Employing a qualitative phenomenological approach, the study explores business actors' and consumers' experiences regarding how Islamic values and pilgrim community interactions influence product value perception and purchasing. The findings indicate that community support rooted in Islamic faith plays a central role; verbal interactions and recommendations based on ukhuwah islamiyah increase product value and drive transactions. This research contributes to Islamic economics and sharia marketing literature by demonstrating how value co-creation is strengthened through religious communities, offering guidance for businesses operating in religio-centric markets.